Crisis management in Sino-American relations 1999-2009 : patterns, changes and prospects - Chan, Boh Yee (2011)
Sino-US relations is said to be the most important bilateral relations in the 21st century. Yet despite deepening Sino-US cooperation over economic and global challenges, military cooperation lagged far behind any progress made as military incidents still occurred frequently. This suggests a harbinger of risks to the rest of the world and this subject warrants closer study. This dissertation addresses the puzzle of "recurring military crises despite warming Sino-US cooperation in non military fields" in the context of three politico-military incidents occurring between 1999 and 2009. A conceptual framework is developed from Brecher's crisis model and Swaine's analytical framework to capture a multilevel analysis. Each case study is analysed in terms of several historical phases: (a) status of exiting bilateral ties, (b) crisis trigger (military incident), (c) dyadic interaction (crisis escalation and de-escalation) and (d) post-crisis status of bilateral ties. The dissertation concludes that a pattern of politicization of military incident persisted at the expense of adopting safe navigational measures. Besides, little was known to Washington that Chinese response – wavering between compromise and resistance – was largely constrained by the interplay of variables such as domestic political stability, its quest for global power, civil-military gap and the People’s Liberation Army (PLA)’s assertiveness. Moreover, Chinese strategic mindset of deception suggests the futility of the US Department of Defence (DOD)’s efforts to engage the PLA in dialogue and joint exercises. Also, Sino-US crisis management is marked by bargaining on core interests rather than conflict resolution. Finally, Beijing’s changing response to the three military incidents also suggests that China’s rise, contrary to its rhetoric, is less than peaceful.